Bringing Governance Back Home - Lessons for Local Government regarding Rapid Climate Action - Tyfield, David; Willis, Rebecca; Yuille, Andy (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
There is a growing recognition that rapid action in response to climate change is urgently necessary, and that many of the responsibilities for this action (e.g., relating to transport, land-use planning and economic development) rest at the local level. This is attested to by the growing number of local authorities that have declared climate emergencies across the globe. Responding to this emergency will require significant changes in the assumptions, expectations, priorities and procedures of locally elected representatives and government officials. This Special Issue will explore the responses of local government, as a key locus of sustainability governance, to the need for rapid climate action, drawing on examples from diverse locations (UK, western Europe, Chile and South Africa) and at various scales (from the smallest local areas, to city regions, counties and provinces).